A Fluorescent Activatable AND‐Gate Chemokine CCL2 Enables In Vivo Detection of Metastasis‐Associated Macrophages. (11th October 2019) - Fernandez, Antonio; Thompson, Emily J.; Pollard, Jeffrey W.; Kitamura, Takanori; Vendrell, Marc
Abstract: We report the novel chemical design of fluorescent activatable chemokines as highly specific functional probes for imaging subpopulations of immune cells in live tumours. Activatable chemokines behave as AND‐gates since they emit only after receptor binding and intracellular activation, showing enhanced selectivity over existing agents. We have applied this strategy to produce mCCL2‐MAF as the first probe for in vivo detection of metastasis‐associated macrophages in a preclinical model of lung metastasis. This strategy will accelerate the preparation of new chemokine‐based probes for imaging immune cell function in tumours. Abstract : Liveshow : Fluoreszierende aktivierbare Chemokine wurden als erste chemische Sonden zum In‐vivo‐Nachweis von tumorassoziierten Makrophagen bei Lungenmetastasen entwickelt. Aktivierbare Chemokine verhalten sich wie AND‐Gatter, da sie erst nach Rezeptorbindung und intrazellulärer Aktivierung emittieren, und weisen eine höhere Selektivität als bisherige Agentien auf.